Cataract and genetic diseases - Mateusz Kozik; Nina Skalska-Dziobek; Weronika Małagocka; Maria Rozpłoch-Sapa; Karolina Chybowska; Mateusz Orłowski; Maria Naruszewicz; Przemysław Cetnarowski; Aleksandra Midro; Karol Zagórski (Quality in Sport, 2024)
Despite the decreasing number of cases, cataract is still the leading cause of visual impairment and blindness worldwide. The search for the causes of this disease, its risk factors and the relationship with systemic diseases is the subject of many studies and attracts the attention of scientists around the world. One of the most common cause of cataract and probably the most frequently reported in the literature, is aging. Other commonly described causes of cataracts are external factors and acquired diseases. Although genetic diseases are not the most common disorders associated with the occurrence and development of cataract, this review takes a broader look at this particular aspect, describing the relationship between cataracts and a group of genetic diseases.